Screw elastic intramedullary nail for the management of adult forearm fractures - Gadegone, Wasudeo (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The failure of the conventional nailing of both forearm bones or isolated fractures of radius and ulna pose a potential problem of nail migration and rotational instability, despite the best reduction. The purpose of this paper is to evaluate the results of screw elastic intramedullary nail for the treatment of adult diaphyseal fractures of both forearm bones, which effectively addresses the problems associated with the conventional nailing systems for the forearm fractures. MATERIALS AND METHODS: Seventy-six adults with forearm fractures (radius and ulna or isolated fracture of the single bone) were retrospectively evaluated. Fifty males and 26 females with the mean age of 38 years (range, 18-70 years) underwent closed reduction and screw intramedullary nail fixation. Ten patients required limited open reduction. The fractures were classified according to the AO/OTA system. The average followup was 12 months (range, 6 to 18 months). RESULTS: The mean surgical time was 45 minutes (35 to 65 minutes). The meantime to union was 14 weeks (10-21 weeks). The results were graded as excellent in 50, good in 18 patients, and acceptable in eight patients, using the criteria of Grace and Eversman. We had superficial infection in three cases, one case of delayed infection, painful bursa in two cases, delayed union in two cases, malunion with dislocation of the DRUJ in two cases, injury to the extensor tendon of the thumb in one case, and one case of incomplete radioulnar synostosis. CONCLUSION: Closed reduction and internal fixation of forearm fractures by screw intramedullary nails reestablishes the near normal relationship of the fractured fragments. Screw intramedullary nail effectively controls both rotatory forces and the migration of the nail. It produces excellent clinical results in isolated fractures of either bones, as well as both bones of the forearm in adults.